Advances in diagnostic assays for Clostridioides difficile infection in adults - Liu, Dong-ang; Chen, Shiyu; Hu, Ruiyao; Qiu, Yuting; Chen, Keyi; Xu, Yue; Yuan, Jinghua; Zhang, Xinling; Li, Xiaoping (Frontiers in Cellular and Infection Microbiology, 2024)
Clostridioides difficile (C. difficile) was a gram-positive anaerobic bacterium in the gut, exhibiting clinical manifestations ranging from mild diarrhoea to fatal pseudomembranous colitis. C. difficile infection (CDI) remains a serious public health problem and accounted for an estimated 360,075 cases in the United States in 2021. It has attracted the utmost attention of the world health organization (WHO). Since publication of a review of the diagnosis of CDI in adults, new clinical diagnostic assays have become available and clinical practice guidelines were updated. This paper presents a comprehensive review of contemporary laboratory diagnostic approaches for CDI in adult patients, with a focus on the utilisation and potential advancements of five sophisticated methodologies, CRISPR in conjunction with nucleic acid amplification tests (NAATs), gene sequencing technology, ultra-high performance liquid chromatography-mass spectrometry, Raman spectroscopy, and real-time cell analysis (RTCA). It can provide new perspectives and ideas for the early diagnosis of CDI in clinical settings.